Waste Banks: Social Capital in Community-Based Sustainable Waste Management Efforts in Padang City - Mabrukah Tomimi, Zahran; Yoserizal, Yoserizal; Aromatica, Desna; Yulivestra, Malse; Wahyuni, Nila; Aulia Putri, Anisa (Iapa Proceedings Conference, 2024)
The waste bank is a creative way to improve behavior and understanding about managing waste in the home. Social capital, as a collaborative effort at the community level, is essential to the trash bank's management. Mutual trust in society, standards, and networks that the community may use to address problems together are known as social capital. This research aims to find out how the social capital process in the Waste Bank framework in community- based sustainable waste management in Padang City, especially in the Sakinah Waste Bank by using descriptive research conducted through a qualitative approach. The study's analysis revealed that the social capital process at Sakinah Waste Bank is carried out by the community, and that trust is developed between the actors through the transparency of the waste bank management process. Strategies to develop networking with the actors include communication, a shared commitment to support the waste bank management, and a shared understanding of the waste bank's purpose. Social norms are necessary to keep the actors' trust in one other and the transparency process going. Additionally, the social norm might raise citizens' awareness of the need to control household waste.